 Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
`        tan60°-tan30°---------------------=tan30°1+tan60°. tan30°`
2 years ago

```							Answer is” tan-1[1+ square root of 3] /2Given , = tan600-[tan300][X]=tan300+tan600.tan300=square root of 3-1/ square root of 3[X]=1/ square root of 3+[ square root of 3.1/ square root of 3]  …. [CANCEL]=[3-1] / square root of 3[X]=1/ square root of 3 +1=finally we get, X =[1+ square root of 3] /2
```
2 years ago
```							 Answer is” tan-1[1+ square root of 3] /2Given , = tan600-[tan300][X]=tan300+tan600.tan300=square root of 3-1/ square root of 3[X]=1/ square root of 3+[ square root of 3.1/ square root of 3]  …. [CANCEL]=[3-1] / square root of 3[X]=1/ square root of 3 +1=finally we get, X =[1+ square root of 3] /2
```
2 years ago
```							 Answer is” tan-1[1+ square root of 3] /2Given , = tan600-[tan300][X]=tan300+tan600.tan300=square root of 3-1/ square root of 3[X]=1/ square root of 3+[ square root of 3.1/ square root of 3]  …. [CANCEL]=[3-1] / square root of 3[X]=1/ square root of 3 +1=finally we get, X =[1+ square root of 3] /2
```
2 years ago
```							 Answer is” tan-1[1+ square root of 3] /2Given , = tan600-[tan300][X]=tan300+tan600.tan300=square root of 3-1/ square root of 3[X]=1/ square root of 3+[ square root of 3.1/ square root of 3]  …. [CANCEL]=[3-1] / square root of 3[X]=1/ square root of 3 +1=finally we get, X =[1+ square root of 3] /2
```
2 years ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Trigonometry

View all Questions »  ### Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution  ### Course Features

• 31 Video Lectures
• Revision Notes
• Test paper with Video Solution
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Previous Year Exam Questions